PROSEDUR AUDIT ATAS HUTANG USAHA PT. AL OLEH KANTOR AKUNTAN PUBLIK SLAMET RIYANTO, ARYANTO, DAN REKAN - Ika Indarista, (2021)
This Final Project Report discusses the audit procedures for PT AL trade payables engaged in Construction. Services that provide infrastructure for Construction. Accounts payable are an important enough account in the financial statements, and to ensure whether the trade payables are presented fairly. The auditor also conducts program audits based on the provisions of the Slamet Riyanto, Aryanto and Partner Public Accountant Firms. It can be concluded that the account of accounts payable at PT AL was not found to be misstated so that it has been presented fairly in all material respects in accordance with accounting standards in force in Indonesia.